Question and Answers Forum

All Questions      Topic List

Algebra Questions

Previous in All Question      Next in All Question      

Previous in Algebra      Next in Algebra      

Question Number 209240 by Jubr last updated on 05/Jul/24

If  x  +  ((49)/(x + 48))  =  − 34  find  (2x + 83)^3  + (1/((2x + 83)^3 ))

$${If}\:\:{x}\:\:+\:\:\frac{\mathrm{49}}{{x}\:+\:\mathrm{48}}\:\:=\:\:−\:\mathrm{34} \\ $$$${find}\:\:\left(\mathrm{2}{x}\:+\:\mathrm{83}\right)^{\mathrm{3}} \:+\:\frac{\mathrm{1}}{\left(\mathrm{2}{x}\:+\:\mathrm{83}\right)^{\mathrm{3}} } \\ $$

Answered by som(math1967) last updated on 05/Jul/24

x+48+((49)/(x+48))=−34+48  ⇒ a+((49)/a)=14 [let x+48=a]  ⇒a^2 −14a+49=0  ⇒(a−7)^2 =0  ∴a=7  ⇒x+48=7  ⇒x=−41  ⇒2x=−82  ⇒2x+83=1  ∴(2x+83)+(1/((2x+83)))=1+1   y+(1/y)=2  [let (2x+83)=y]  (y+(1/y))^3 =8  ⇒y^3 +(1/y^3 ) +3.y.(1/y)(y+(1/y))=8  ⇒y^3 +(1/y^3 )=8−3×2=2  ∴(2x+83)^3 +(1/((2x+83)^3 ))=2

$${x}+\mathrm{48}+\frac{\mathrm{49}}{{x}+\mathrm{48}}=−\mathrm{34}+\mathrm{48} \\ $$$$\Rightarrow\:{a}+\frac{\mathrm{49}}{{a}}=\mathrm{14}\:\left[{let}\:{x}+\mathrm{48}={a}\right] \\ $$$$\Rightarrow{a}^{\mathrm{2}} −\mathrm{14}{a}+\mathrm{49}=\mathrm{0} \\ $$$$\Rightarrow\left({a}−\mathrm{7}\right)^{\mathrm{2}} =\mathrm{0} \\ $$$$\therefore{a}=\mathrm{7} \\ $$$$\Rightarrow{x}+\mathrm{48}=\mathrm{7} \\ $$$$\Rightarrow{x}=−\mathrm{41} \\ $$$$\Rightarrow\mathrm{2}{x}=−\mathrm{82} \\ $$$$\Rightarrow\mathrm{2}{x}+\mathrm{83}=\mathrm{1} \\ $$$$\therefore\left(\mathrm{2}{x}+\mathrm{83}\right)+\frac{\mathrm{1}}{\left(\mathrm{2}{x}+\mathrm{83}\right)}=\mathrm{1}+\mathrm{1} \\ $$$$\:{y}+\frac{\mathrm{1}}{{y}}=\mathrm{2}\:\:\left[{let}\:\left(\mathrm{2}{x}+\mathrm{83}\right)={y}\right] \\ $$$$\left({y}+\frac{\mathrm{1}}{{y}}\right)^{\mathrm{3}} =\mathrm{8} \\ $$$$\Rightarrow{y}^{\mathrm{3}} +\frac{\mathrm{1}}{{y}^{\mathrm{3}} }\:+\mathrm{3}.{y}.\frac{\mathrm{1}}{{y}}\left({y}+\frac{\mathrm{1}}{{y}}\right)=\mathrm{8} \\ $$$$\Rightarrow{y}^{\mathrm{3}} +\frac{\mathrm{1}}{{y}^{\mathrm{3}} }=\mathrm{8}−\mathrm{3}×\mathrm{2}=\mathrm{2} \\ $$$$\therefore\left(\mathrm{2}{x}+\mathrm{83}\right)^{\mathrm{3}} +\frac{\mathrm{1}}{\left(\mathrm{2}{x}+\mathrm{83}\right)^{\mathrm{3}} }=\mathrm{2} \\ $$

Commented by Frix last updated on 05/Jul/24

Yes!  But  2x+83=1 ⇒ (2x+83)^n +(1/((2x+83)^n ))=2  without any further calculations.

$$\mathrm{Yes}! \\ $$$$\mathrm{But} \\ $$$$\mathrm{2}{x}+\mathrm{83}=\mathrm{1}\:\Rightarrow\:\left(\mathrm{2}{x}+\mathrm{83}\right)^{{n}} +\frac{\mathrm{1}}{\left(\mathrm{2}{x}+\mathrm{83}\right)^{{n}} }=\mathrm{2} \\ $$$$\mathrm{without}\:\mathrm{any}\:\mathrm{further}\:\mathrm{calculations}. \\ $$

Commented by Spillover last updated on 05/Jul/24

perfect

$${perfect} \\ $$

Commented by Tawa11 last updated on 05/Jul/24

Thanks sir. I appreciate.

$$\mathrm{Thanks}\:\mathrm{sir}.\:\mathrm{I}\:\mathrm{appreciate}. \\ $$

Terms of Service

Privacy Policy

Contact: info@tinkutara.com